2012
DOI: 10.1002/anie.201205075
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Revealing the Packing in Semicrystalline π‐Conjugated Polymers: Crystal Structure of Bulk Poly‐3‐hexyl‐thiophene (P3HT)

Abstract: To tilt or not to tilt: The crystal structure for bulk P3HT (phase I) was determined by "multi-technique crystallography", which combines X-ray diffraction, solid-state NMR spectroscopy, and DFT calculations. The results showed that this semiconducting polymer crystallizes in the monoclinic space group P2(1)/c with nontilted π-stacks at a distance of 3.9 Å (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
183
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(218 citation statements)
references
References 51 publications
22
183
1
Order By: Relevance
“…59 However, a key requirement for the 2D The broad 1 H line width of the thiophene proton is a result of restricted molecular mobility of several P3TMAHT chains sticking together in addition to the spatial overlap between the π-conjugated chains, leading to a shift to lower frequency (or equivalently a high-field shift). 60 This is in agreement with the neutron and light scattering studies on aqueous solutions of P3TMAHT suggesting that the chains aggregate with interparticle order. 40,61 Mixing P3TMAHT with CLP in D 2 O gives the 1 H NMR spectrum in Figure 4b.…”
Section: ■ Experimental Methodssupporting
confidence: 85%
“…59 However, a key requirement for the 2D The broad 1 H line width of the thiophene proton is a result of restricted molecular mobility of several P3TMAHT chains sticking together in addition to the spatial overlap between the π-conjugated chains, leading to a shift to lower frequency (or equivalently a high-field shift). 60 This is in agreement with the neutron and light scattering studies on aqueous solutions of P3TMAHT suggesting that the chains aggregate with interparticle order. 40,61 Mixing P3TMAHT with CLP in D 2 O gives the 1 H NMR spectrum in Figure 4b.…”
Section: ■ Experimental Methodssupporting
confidence: 85%
“…These 13 C aggregation shifts could provide valuable constraints for the determination of the P3HT crystal lattice geometry, supplementing information provided by the well-studied 1 H aggregation shifts. 17,38 The assignment of crystalline 13 C peaks could also be used to determine crystallinity. Nieuwendaal et al reported that the signals from ordered domains exhibit longer T 1ρ than those from the disordered region.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This technique offers access to these molecular scale properties via the proton ( 1 H) and carbon ( 13 C) chemical shis as reected in their isotropic chemical shis and resonance line widths. 16 Here, we further exploit the different T 2 -relaxation properties of the crystalline and amorphous regions of the polymers by applying the refocused 18 or the through space dipole-dipole coupling, respectively, allowing us to differentiate between rigid and exible regions of the polyesters. Fig.…”
mentioning
confidence: 99%